Perancangan Aplikasi Android Edukasi Huruf dan Angka Berbasis Audio Interaktif Menggunakan Metode Multimedia Development Life Cycle pada SD Negeri 59/1 Durian Luncuk - Desvita Resdianti; Albet Triadi (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The development of information technology has had a significant impact on the field of education, including early childhood learning. Learning letters and numbers is a fundamental stage in building children’s literacy and numeracy skills. Based on observations and interviews conducted at SD Negeri 59/1 Durian Luncuk, the learning process for letters and numbers still relies on card-based media and verbal explanations from teachers, making the learning activities less interactive and causing children to become easily bored. In addition, there is no technology-based learning media that can be used independently by children. Therefore, this study aims to design and develop an Android-based educational application for learning letters and numbers with interactive audio that is attractive, easy to use, and suitable for the characteristics of early childhood learners. The application presents learning materials for letters A–Z and numbers 1–10, complemented by pronunciation audio, simple animations, and quiz features as a learning evaluation tool. The development method used in this study is the Multimedia Development Life Cycle (MDLC), which consists of the concept, design, material collecting, assembly, testing, and distribution stages. The application was developed using Android Studio with Java and XML programming languages. System testing was conducted using the Black Box Testing method to ensure that all functions operate according to requirements. The results show that the application runs properly and helps increase children’s interest and understanding in learning letters and numbers. Keywords: Android Application, Interactive Audio, Education, Multimedia Development Life Cycle.